Fine Particulate Matter and Gaseous Compounds in Kitchens and Outdoor Air of Different Dwellings - Alves, C (2020)
Passive diffusion tubes for volatile organic compounds (VOCs) and carbonyls and low volume particulate matter (PM2.5) samplers were used simultaneously in kitchens and outdoor air of four dwellings. PM2.5 filters were analysed for their carbonaceous content (organic and elemental carbon, OC and EC) by a thermo-optical technique and for polycyclic aromatic hydrocarbon (PAHs) and plasticisers by GC-MS. The morphology and chemical composition of selected PM2.5 samples were characterised by SEM-EDS. The mean indoor PM2.5 concentrations ranged from 14 µg m-3 to 30 µg m-3, while the outdoor levels varied from 18 µg m-3 to 30 µg m-3. Total carbon represented up to 40% of the PM2.5 mass. In general, the indoor OC/EC ratios were higher than the outdoor values. Indoor-to-outdoor ratios higher than 1 were observed for VOCs, carbonyls and plasticisers. PAH levels were much higher in the outdoor air. The particulate material was mainly composed of soot aggregates, fly ashes and mineral particles. The hazard quotients associated with VOC inhalation suggested a low probability of non-cancer effects, while the cancer risk was found to be low, but not negligible. Residential exposure to PAHs was dominated by benzo[a]pyrene and has shown to pose an insignificant cancer risk.